Outcome devaluation by specific satiety disrupts sensory-specific Pavlovian-to-instrumental transfer - Panayi, Marios C.; Killcross, Simon (Frontiers in Behavioral Neuroscience, 2022)
Reward predictive cues can selectively motivate instrumental behaviours that predict the same rewarding outcomes, an effect known as specific Pavlovian-to-instrumental transfer (PIT). This selective effect is thought to be mediated by a representation of the sensory specific properties of an outcome, that has become associated with both the Pavlovian cue and the instrumental response during initial learning. Specific satiety is a common method of outcome devaluation that reduces an outcome’s value but might also lead to the habituation of the outcome’s sensory properties. Previous research has demonstrated that specific PIT is insensitive to changes in specific outcome value following taste aversion devaluation, as well as general satiety manipulations, and therefore specific satiety should not disrupt specific PIT by reducing outcome value. The present rodent experiments used a specific satiety devaluation procedure immediately prior to a specific PIT test to show that habituation of these outcome specific sensory representations can disrupt its efficacy as a stimulus and abolish the specific PIT effect. Experiment 1 employed a two-lever choice test to show that a non-devalued stimulus supports specific PIT, whereas a devalued stimulus abolished the specific PIT effect. Experiment 2 replicated this procedure while controlling for response competition by using a single-lever test to confirm that a devalued stimulus abolishes the specific PIT effect. These findings demonstrate that specific satiety can disrupt the ability of an outcome specific representation to support specific PIT. Given previous findings that specific PIT is insensitive to changes in outcome value by general satiety and taste aversion devaluation, this suggests that specific satiety devaluation might disrupt the use of sensory specific outcome representations to guide behaviour via a mechanism that is independent of the outcome’s current value.